Analisa pengaruh pertambangan terhadap peningkatan mutu pendidikan di Dusun Tani Jaya PT. Baramulti Suksessarana Kalimantan Timur (Jurnal Geologi Pertambangan (JGP), 2021)
ABSTRACT The results showed that the regression test with significant level 10% atau 0,10, obtained a regressive equation Y = 2,707 + 0,761 X which was used as a basis to predict improving the quality of education influenced by the presence of the mining. The calculation of hypothesis utilized t-test of significant level at 10% or 0,10 based on the formula (thitung = 4,875 > ttabel = 1,15). Which presented that the accurate independent variabel proved significantly. Then, according to F test based on the value (Fhitung = 23,770 > Ftabel = 9,63), it can be seen that the independent variable can be used to examine improving the quality of education. Figure adjusted R square 0,487 demonstrated 4,8%, eventually this research explained that the variable of the mining presence impacted remarkably on improving the quality of education. Kata kunci: Pengaruh pertambangan, Pengembangan dan Pemberdayaan Masyarakat (PPM), Statistik Regresi Linear